Offense Narrative Roles of Turkish Offenders - Zeyrek-Rios, Emek Yuce (International journal of offender therapy and comparative criminology, 2022)
The study of offense narratives emphasizes the agency of the offender which brings psychology closer to law. As an effort to create a standardized and quantitative method to evaluate offender narratives, Youngs and Canter developed the Narrative Roles Questionnaire (NRQ) based on the content analyses of the crime narratives of offenders in UK prisons. The current study aims to investigate the applicability of offense narrative roles framework among Turkish offenders. The application of the offense narrative roles model to a non-Western country is the first step toward the acceptance of criminal narrative theory as a universal explanation of criminal behavior. A translation of the NRQ was administered to 468 Turkish male inmates who have committed a wide range of offenses from fraud to murder. The results of an MDS analysis yielded four roles, namely Professional, Revenger, Hero, and Victim, echoing the original formulation proposed by Youngs and Canter. The reliability coefficients of scales derived for these roles were all at desired levels. The results support the applicability of the NRQ framework in a non-English context.